Understanding the oxidation of the tricarbon radical C3H: A reaction pathway survey. Issue 23 (13th June 2013) - Zhu, Wei‐Wei; Jin, Lin; Cui, Zhong‐Hua; Zhang, Shao‐Wen; Ding, Yi‐Hong
<x xml:space="preserve">Abstract</x> The very recent observation of molecular oxygen in interstellar space appeals for the great need of mechanistic understanding of the oxidation processes of various interstellar species. In this article, we report for the first time, the oxidation mechanism of the chainlike l‐C3H by molecular oxygen, which is known as one of the interesting carbon‐chain hydrocarbon series CnH detected in space. This reaction is also relevant to the combustion processes where various carbon hydrides are involved. The detailed reaction pathways were identified at the CCSD(T)/aug‐cc‐pVTZ//B3LYP/6‐311++G(d, p)+ZPVE level including various fragmentation channels. Three types of fragmentation channels are identified as the C‐transfer product P2 (CO2+C2H) (−129.2kcal/mol), the C, O‐exchange product P1 (CO+HC2O) (−154.7kcal/mol), and the O‐transfer product P6 (3O+HC3O) (−44.8kcal/mol). The initially entered unstable dioxygen isomer 1a HCCCOO (−26.6 kcal/mol) would either undergo the direct O‐extrusion to give P6 (the intrinsic barrier 7.5 kcal/mol) or take a 1, 2‐O‐shift (0.8 kcal/mol barrier) to give a stable isomer 5 HCCC(O)O (−139.2kcal/mol) that can either dissociate to P1 or to P2. The intrinsic barrier from 5 to P1 and P2 is 29.1 and 23.6 kcal/mol, respectively. Clearly, the entrance thermicity 26.6 kcal/mol of 1a can sufficiently initiate the subsequent formation of all the three products. To quantitatively evaluate the kinetic competition of the three products, we performed the master equation rate constant calculations. It was shown that at 298 K, the most favorable product is P2 (64.8%) followed by P6 (23.6%), and P1 (11.6%). Interestingly, at elevated temperatures, the ratio of P6 increases with the decrease of P2, whereas that of P1 is little changed. Notably, the thermodynamically most stable product P1 is kinetically the least favorable, indicative of the importance of considering the kinetics. The dominant formation of P2 (CO2+C2H) shows that the important carbyne radical l‐C3H can be effectively degraded by O2 via the chain‐shortening step. The reactivity of the cyclic c‐C3H radical toward O2 is also discussed. The results are expected to enrich our understanding of the chemistry of the simplest C3‐radical in both combustion and interstellar processes. © 2013 Wiley Periodicals, Inc.